2015
DOI: 10.4254/wjh.v7.i7.954
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B reactivation in the setting of chemotherapy and immunosuppression - prevention is better than cure

Abstract: in the setting of chemotherapy and immunosuppression may lead to fulminant liver failure and death, but there is a cumulative body of evidence that these are potentially preventable adverse outcomes. As chronic hepatitis B is largely asymptomatic but also endemic worldwide, clinicians caring for patients requiring chemotherapy or immunosuppression need to be vigilant of the potential for HBVr in susceptible individuals. Serological screening and prophylactic and pre-emptive antiviral treatment with a nucleos(t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 106 publications
0
32
0
3
Order By: Relevance
“…Amennyiben felmerül hepatitis B-fertőzés (HBsAg-pozitív vagy anti-HBc-pozitív), akkor antivirális profilaxist kell alkalmazni [23]. A vírus-DNS monitorozása is javasolt alacsony rizikó esetén, de ÖSSZEFOGLALÓ KÖZLEMÉNY bizonyítottan nem annyira hatásos a kezelés elkezdése emelkedő vírustiter esetén, mint ha profilaxist kapott volna a beteg [23]. A hepatitis C-pozitív esetekben szintén indokolt vírus-RNS-PCR, de a reaktiváció veszélye C-vírus esetén nem annyira jelentős.…”
Section: A Dlbcl Kezelése Maunclassified
“…Amennyiben felmerül hepatitis B-fertőzés (HBsAg-pozitív vagy anti-HBc-pozitív), akkor antivirális profilaxist kell alkalmazni [23]. A vírus-DNS monitorozása is javasolt alacsony rizikó esetén, de ÖSSZEFOGLALÓ KÖZLEMÉNY bizonyítottan nem annyira hatásos a kezelés elkezdése emelkedő vírustiter esetén, mint ha profilaxist kapott volna a beteg [23]. A hepatitis C-pozitív esetekben szintén indokolt vírus-RNS-PCR, de a reaktiváció veszélye C-vírus esetén nem annyira jelentős.…”
Section: A Dlbcl Kezelése Maunclassified
“…The rate of hepatitis B virus reactivation events in the setting of chronic airways disease due to chronic oral vs. inhaled steroid use is 11.1% and 3.2%, respectively. 9 The magnitude of risk of hepatitis B virus reactivation Ulfa Kholili, Tri Yanti…”
Section: Chemotherapeutic Agents Associated With Hepatitis B Virus Rementioning
confidence: 99%
“…For instance, rituximab, is an agent predominantly used to treat haematological malignancy in addition to autoimmune and neurological disease. 9,10 Rituximab is an agent that works against CD20 on B-cell. CD20 positive B-cells depletion might reduce the number of CD4 memory cells, CD8 cells, and antibody-mediated immunity.…”
Section: Chemotherapeutic Agents Associated With Hepatitis B Virus Rementioning
confidence: 99%
“…Corticosteroids are the most longstanding and hence most commonly used of the immunosuppressants. In addition to their effect on T-cell function, corticosteroids directly enhance HBV replication through the interaction with the HBV glucocorticoid responsive element (a transcriptional regulatory element) [25][26] . Although steroids are administered at a range of dosages and durations for a variety of indications, it has been observed that a 4-week course of prednisone in a dosage higher than 20 mg has been associated with high risk (> 10 %) of HBV reactivation in the post-withdrawal (immune reconstitution) phase and worsened liver histology [26][27] .…”
mentioning
confidence: 99%
“…In addition to their effect on T-cell function, corticosteroids directly enhance HBV replication through the interaction with the HBV glucocorticoid responsive element (a transcriptional regulatory element) [25][26] . Although steroids are administered at a range of dosages and durations for a variety of indications, it has been observed that a 4-week course of prednisone in a dosage higher than 20 mg has been associated with high risk (> 10 %) of HBV reactivation in the post-withdrawal (immune reconstitution) phase and worsened liver histology [26][27] . Our patient was on the constant IS therapy with prednisone (dosage of 30 mg per day and more for more than initial month after TX and 5 mg daily from the sixth month after TX and ongoing), from 2008 until 2017, during a span of 9 years, and HBV reactivation has not occurred yet.…”
mentioning
confidence: 99%